2008
DOI: 10.1080/02640410802277445
|View full text |Cite
|
Sign up to set email alerts
|

In-school and out-of-school physical activity in primary and secondary school children

Abstract: The aim of this study was to compare in-school and out-of-school physical activity within a representative sample. Socio-demographic, physical activity, and anthropometric data were collected from a random sample of children (250 boys, 253 girls) aged 3-16 years attending nine primary and two secondary schools. Actigraph GT1M accelerometers, worn for seven days, were used to estimate physical activity levels for in-school (typically 09.00-15.00 h), out-of-school (weekday), and weekend periods. Physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
75
2
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 38 publications
11
75
2
7
Order By: Relevance
“…This study excluded and the HBSC survey included school activities such as school sports in the physical activity assessment. Since, overall, physical activity during the school day appears to be lower than that out of school [17], African children seem still to be less physically active than Euro-North American children. This study found cross-national variations in the prevalence of frequent leisure time physical activity, Ugandan and Kenyan school children were most frequently physically active (17.7% and 16.0%, respectively) and Zambian and Senegalese school children the least (9.0% and 10.9%, respectively).…”
Section: Discussionmentioning
confidence: 80%
“…This study excluded and the HBSC survey included school activities such as school sports in the physical activity assessment. Since, overall, physical activity during the school day appears to be lower than that out of school [17], African children seem still to be less physically active than Euro-North American children. This study found cross-national variations in the prevalence of frequent leisure time physical activity, Ugandan and Kenyan school children were most frequently physically active (17.7% and 16.0%, respectively) and Zambian and Senegalese school children the least (9.0% and 10.9%, respectively).…”
Section: Discussionmentioning
confidence: 80%
“…Gidlow et al (2008) reported that PA levels during the school day appeared to be lower than when out of school, especially for secondary school children, who accumulated a lower proportion of their total weekly moderate-to-vigorous physical activity at school than younger children. In our study, the in-and out-of school PA levels were not separated.…”
Section: Day Of the Weekmentioning
confidence: 95%
“…Schools provide a unique opportunity to help children and adolescents to accumulate physical activity within the school day to benefit their health (Cale and Harris, 2006). Several studies have found that children are more active during school days (Falgairette et al, 1996;Gavarry et al, 1998Gavarry et al, , 2003Rowlands et al, 2008;Sleap and Warburton, 1996) while others reported higher PA levels during free days (Duncan et al, 2006;Gidlow et al, 2008;Pate et al, 1994;Trost et al, 2000) or no difference according to the day of the week (Gilbey and Gilbey, 1995;Salo and Silla, 1997;Taylor et al, 2009). These discrepancies may be due to differences in time spent at school or in time organization at school between countries.…”
mentioning
confidence: 93%
“…As children spend a large period of their day at school, it would seem schools could be a vital link in the promotion of physical activity and the prevention of overweight and obesity 10 14 15. Schools reach almost every child, including those who are most at risk, for a large period of their lives 1 16.…”
mentioning
confidence: 99%